1968
DOI: 10.1111/j.1440-1673.1968.tb01566.x
|View full text |Cite
|
Sign up to set email alerts
|

Urographic Excretion Study.

Abstract: Previous papers have suggested that a maximum urinary radioopacity is achieved in mail when an adequate dose of contrast agent is given after suitable dehydration (Benness, 19651, and that this maximum radioopacity may be rclatrd to renal function (Henness et al., 1965). This concept has been confirmed in the laboratory using sheep (Renness, 3967), and the work has heen continued to define the influence of different urographic agents on urinary radioopacity. MATERIALS .mi) METHODSX method of controlling the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

1970
1970
2003
2003

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…At higher doses, especially at 640 mg I/kg body weight during ureteral occlusion, and more markedly in estimated density than in urinary iodine concentration, the sodium salt is, however, the superior. Benness (1968Benness ( & 1970 obtained a higher urinary iodine concentration when applying sodium salt than meglumine salt. In his experiments, however, Benness used considerably longer sampling periods, and did not apply ureteral occlusion.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…At higher doses, especially at 640 mg I/kg body weight during ureteral occlusion, and more markedly in estimated density than in urinary iodine concentration, the sodium salt is, however, the superior. Benness (1968Benness ( & 1970 obtained a higher urinary iodine concentration when applying sodium salt than meglumine salt. In his experiments, however, Benness used considerably longer sampling periods, and did not apply ureteral occlusion.…”
Section: Discussionmentioning
confidence: 90%
“…1970;Benness 1970;Benness & Glazer 1973;Dacie & Fry 1971). This is thought to be due to the greater urinary solute load produced by the meglumine agent because of the added excretion of the non-opaque meglumine ion (Benness 1968;Evil1 & Benness 1975b). According to our experiments, the sodium salt of diatrizoate in adose up to 320 mg I/kg body weight is not superior to the meglumine salt.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…T h e dosage of contrast agent is the most important single factor in determining the final urinary iodine concentration. Concerning contrast agents, experiments (Benness, 1968Cattell et al, 1970;Pearson 198 et al, 1971;Dacie and Fry, 1971) showed a higher urinary iodine concentration with sodium salts rather than methylglucamine salts. Benness (1968) suggested that the reason for this is the different osmotic diuretic effects of sodium and methylglucamine ions.…”
Section: Introductionmentioning
confidence: 96%
“…They offered the hypothesis that the preventive effect might be osmotic diuresis. The contrast media used are hyperosmotic and increase the diuresis considerably without any premedication (BENNESS 1968). Metrizamide has, as a non-ionic compound, nominally half the osmotic pressure of the monomer ionic media.…”
mentioning
confidence: 99%